Implementation Effect of Criminal Minimum Penalty into Eradication of Corruption in Makassar - Salim, Agus (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to understand, analyze and find out the implementation effect of minimum criminal penalty into the eradication of corruption in Makassar Indonesia. The type of research that will conduct is descriptive research with the kind of normative legal analysis. This research will include the type of study uses a normative-empirical method of the judicial case study category, which source from primary and secondary data analyzed qualitatively descriptive. The results of the research that show, it was concluded that that could be carrying out the legislative order, the judge may impose a minimum crime because this stipulates in the law. The judge is in charge of carrying out the act. Furthermore, minimal criminal imposes concerning efforts to tackle corruption does not create a deterrent effect for corruptors. It cannot be a useful tool to prevent crime both of a particular (Special Prevention) and general nature (General Prevention).